PENGARUH KEBIJAKAN DIVIDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP KEPUTUSAN PEMBIAYAAN PADA PERUSAHAAN TERDAFTAR DI BEI TAHUN 2013 DENGAN FIRM SIZE SEBAGAI VARIABEL KONTROL - Astari, Arum Dwi; Yetty, Fitri (Ekonomi dan Bisnis, 2015)
This study is performed to examine the effect of variable dividend policy and managerial ownership toward financing decision in company listed in BEI at 2013 with firm size as control variable. The population in this study is listed company in Indonesia Stock Exchange at 2013. Gained a total sample of 52 companies. The analysis technique used here is multiple linear regression and hypothesis test using F statistic and t statistic with level of significance 5%. The results showed that the dividend policy and managerial ownership in Model 1 and Model 2 does not significantly influence the financing decision. While the control variables of firm size significantly influence financial decisions. We recommend to investors in the Indonesia Stock Exchange in order to pay attention to other factors that influence the financing decisions in making their investment decision. The control variables of firm size in this study is the most influential variable on financing decisions indicated from t-count value is smaller than the table and have significantly by 0.003.